Measurement and Development of Systems Thinking–Empirical Findings Regarding the Structure of System Competence and Its Promotion by Means of Analogue and Digital Models - Brockmüller, Svenja; Siegmund, Alexander (Journal of Geography Education, 2020)
The challenges within the context of global climate change illustrate the relevance of system competence for evaluating complex human-environmental relations. By means of pre-post design this empirical comparison study examines the changes of the contextual systems thinking of students using (1) analogue or (2) digital soil erosion models (simulation), respectively (3) a combination of both approaches. Based on the "Freiburg heuristic competence model of systems thinking", test items are developed and validated. Confirmatory factor analyses suggest a four-dimensional competence structure. Analyses of variance reveal a significant higher mean value of system competence in the group that has experienced a combined analogue and digital intervention compared to the group with mere computer simulation.